SHARIA COMPLIANCE DAN ISLAMIC CORPORATE GOVERNANCE: PENGARUHNYA TERHADAP PENGUNGKAPAN FRAUD - Putra, Muhammad Aditya; Mukhtaruddin (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study explores the influence of Sharia Compliance and Islamic Corporate Governance (ICG) on Fraud disclosure in Islamic commercial banks through the lens of Agency Theory. Sharia Compliance plays a pivotal role in preventing Fraud by enforcing strict Islamic principles of honesty, justice, and transparency, with the Sharia Supervisory Board (SSB) serving as a critical monitoring mechanism. Meanwhile, ICG strengthens internal oversight through structured governance mechanisms, including independent commissioners and frequent SSB meetings, reducing information asymmetry and limiting managerial misconduct. By mitigating agency conflicts and reinforcing ethical business practices, robust Sharia Compliance and ICG frameworks enhance Fraud detection and foster greater corporate transparency. This research highlights the importance of integrating Islamic governance principles to safeguard stakeholder interests and build public trust in the Islamic banking sector.